People, Places, and Perceptions: Assessing Spatial Quality Attributes of Urban Third-place With Projective Survey - Upendra Vinay Joshi; Snehal Nagarsheth (Journal of Contemporary Urban Affairs, 2024)
Urban third places, such as cafes, parks, and plazas, are integral to the social fabric of urban environments, providing spaces for informal social interaction outside of home and work. This study explores the spatial quality attributes that define these third places and their influence on user perceptions and experiences. By employing a projective survey, a qualitative research method utilizing ambiguous stimuli to reveal deeper user sentiments, the research identifies key characteristics that contribute to the desirability of these spaces. Findings highlight the significance of physical, functional, and social dimensions, including furniture design, spatial layout, and opportunities for social interaction. These attributes are shown to vary significantly across different age groups, with notable differences in preferences between younger and older participants. The study's insights inform urban designers and architects on creating inclusive, vibrant third places that enhance urban livability and economic vitality. The research underscores the need for a human-centric approach in urban design, emphasizing the importance of accommodating diverse user needs and preferences to foster a sense of community and well-being in urban settings. By understanding the nuanced relationships between spatial attributes and user perceptions, the study contributes to the development of more effective urban design strategies.